Multiple flow cytometry analysis for assessing human sperm functional characteristics - de Lima Rosa, Josiane [UNESP]; de Paula Freitas Dell'Aqua, Camila [UNESP]; de Souza, Fabiana Ferreira [UNESP]; Missassi, Gabriela [UNESP]; Kempinas, Wilma De Grava [UNESP] (Elsevier, 2023)
Multiparametric analysis by flow cytometry solves one of the major problems in sperm evaluation, the inability to test multiple attributes simultaneously in a single cell, which would increase the precision to predict fertility potential since several sperm parameters are tested. The association of fluorochromes and compounds conjugated to fluorochromes in multiparametric sperm analysis is well-established in microscopy techniques. However, these techniques are subjective and limit the assessment in small cell numbers, thereby harming analytic accuracy. Therefore, the current study aimed to present new possibilities for assessing the integrity and stability of the sperm plasma membrane, acrosome status, mitochondrial potential, and superoxide anion production in the mitochondrial matrix in only 2 cytometric assays using cytometers equipped with 2 and 3 lasers. For this, human semen samples collected by masturbation and selected by the swim-up technique were divided into 3 treatments: T0 (flash-frozen semen), T50 (flash-frozen semen + fresh semen, V: V), and T100 (fresh semen) for the validation of the multiparametric protocols by flow cytometry. For both protocols, sperm percentage with positive stain for all fluorophores differed significantly between treatments. The determination coefficients presented values close to 1, which validated objective, sensitive, rapid, and reproducible methodologies. Therefore, we concluded that the results reflect the status of analyzed structure, enabling a more accurate diagnosis of male infertility that has become an increasingly prevalent worldwide setback due to exposure to a variety of environmental toxicants.
Keywords: Flow cytometry; Human sperm; Male infertility; Multiparametric analysis; Reproductive toxicity